ANALISA KINERJA RUAS DAN TINGKAT PELAYANAN JEMBATAN MAHAKAM ULU (MAHULU) - NI, SUR (KURVA S JURNAL MAHASISWA, 2018)
Transportation plays an important role in the economic, political, cultural, defense and security fields. Because with the transportation of inter-regional relations more smoothly and saving time and costs that are very beneficial for the community. As the population increases, the movement of transportation in the Mahakam Ulu bridge area (Mahulu) increases and influences the segment performance and the service level of the Mahulu bridge. Mahulu Bridge is a bridge that connects Loa Buah Village and Sengkotek Village, Samarinda which stretches over the Mahakam river flow. The purpose of this study was to determine the performance of the sections on the Mahulu bridge that were assessed from the level of service. Analysis carried out manually in accordance with the conditions of traffic flow in Indonesia. In this case an analysis was carried out using the 1997 Indonesian Road Capacity Manual (MKJI’1997) to take into account traffic performance. Traffic volume data is obtained from field surveys conducted for 4 days, namely on Friday, Sunday, Monday and Tuesday, taking into account the level of traffic volume on that day and during peak hours presented in the form of vehicle data tables. Based on the result of the performance analysis of the Mahulu bridge segment which was assessed from the level of service with the MKJI’1997 method, the service level of Mahulu bridge segment at peak hours on Friday and peak hours of Tuesday was C, namely the condition of steady flow, but the speed of operation and movement of the vehicle was greatly affected the traffic volume and service level of the Mahulu Bridge road on Sunday and the peak hours on Monday are B, that is the condition of the current is stable, but the operating speed is limited by traffic conditions, the driver is limited in choosing speed.